Assessing the Association between Oral Hygiene and Preterm Birth by Quantitative Light-Induced Fluorescence - Christopher K. Hope; Qian Wang; Girvan Burnside; Adejumoke A. Adeyemi; Siobhan Quenby; Philip W. Smith; Susan M. Higham; Melissa Whitworth (The Scientific World Journal)
The aim of this study was to investigate the purported link between oral hygiene and preterm birth by using image analysis tools to quantify dental plaque biofilm. Volunteers (n=91) attending an antenatal clinic were identified as those considered to be “at high risk” of preterm delivery (i.e., a previous history of idiopathic preterm delivery, case group) or those who were not considered to be at risk (control group). The women had images of their anterior teeth captured using quantitative light-induced fluorescence (QLF). These images were analysed to calculate the amount of red fluorescent plaque (ΔR%) and percentage of plaque coverage. QLF showed little difference in ΔR% between the two groups, 65.00% case versus 68.70% control, whereas there was 19.29% difference with regard to the mean plaque coverage, 25.50% case versus 20.58% control. A logistic regression model showed a significant association between plaque coverage and case/control status (P=0.031), controlling for other potential predictor variables, namely, smoking status, maternal age, and body mass index (BMI).